ANALISIS PERBANDINGAN UJI SIFAT FISIK KOMPON PACKING PINTU REBUSAN PABRIK KELAPA SAWIT DARI KARET ALAM DAN KARET SINTETIS - Faisal Ab’dau; Busrizal Faizal; Pada Mulia Raja (Jurnal Agro Fabrica, 2021)
This study discusses the quality comparison of the rubber compound that will be used as a door sterilizerpacking. To find the best formulation between natural rubber and synthetic rubber, it is necessary to have theright composition so that when used in the packing compound the sterilizer has resistance when used. Theresults of this study can be known as compound number 2 with the composition of NR 36%, SBR 28%, andNBR 36%. with Tensile Strength Value of 10.6168 Kg/cm², Modulus of Elasticity of 1.4499%, Hardness of68.5 Shore A, and Heat Resistance of 118 ° C which is both used for formulations for making sterilizer doorpacking